Hip Extensor Strength Influences Dynamic Postural Changes during Gait in Patients with Adult Spinal Deformity: A Cross-Sectional Study Using Three-Dimensional Motion Analysis - Keita Sato; Ryoji Tominaga; Tatsuya Endo; Takuya Miura; Masumi Iwabuchi; Toshikazu Ito; Osamu Shirado (Asian Spine Journal, 2022)
Study Design Single-hospital cross-sectional study. Purpose The aim of the present study was to investigate the physical functions influencing dynamic postural change in patients with adult spinal deformity (ASD). Overview of Literature Dynamic postural change leading to increased forward lean during gait is a problem in patients with ASD; however, the relationship between this change and trunk and hip extensor strength is unclear. Methods Thirty patients with ASD aged ≥50 years who were admitted to our hospital between July 2016 and September 2019 were included in this study. X-ray parameters (i.e., sagittal vertical axis, pelvic tilt, and pelvic incidence minus lumbar lordosis) were evaluated from the full-length standing radiographs of the subjects. Trunk and hip extensor strength was evaluated using a hand-held dynamometer. Dynamic postural changes (i.e., sagittal trunk shift during standing, sagittal trunk shift during gait, and delta sagittal trunk shift) were assessed using a three-dimensional motion analysis system. The relationships between dynamic postural change and various X-ray parameters, as well as trunk and hip extensor strength, were examined using multivariable analysis. Results Multivariable analysis showed that hip extensor strength is the factor most strongly associated with dynamic postural change among the X-ray parameters and physical functions assessed in this study (β=−0.41, R2=0.12). Conclusions We demonstrated the association between dynamic postural change and hip extensor strength in patients with ASD. Our results may be useful to healthcare providers treating patients with ASD. Interventions for dynamic postural change in patients with ASD should focus on hip extensor strength.